TURBINES DESIGN FOR HIDROPOWER IN WAY LAAI AND WAY LAMI PESISIR BARAT DISTRICT LAMPUNG PROVINCE - Kiki Kananda; Dean Corio; Efa Maydhona S (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2020)
Hydropower is considered to be one of important renewable energy sources. Renewable energy is the second-largest contributor to global electricity production after fossil fuel. Hydropower generation presents several advantages over most other sources of electrical power. It includes a high level of reliability, proven technology, high efficiency (about 90%), very low operating and maintenance costs, flexibility and large storage capacity. Based on the types of installation, hydropower can be categorized as; impoundment, diversion, and pump storage, and based on the turbine types can it be classified as reaction and impulse systems. Previous research gives the results of the initial survey, concluding that there are two rivers that have the potential to become a micro or mini-hydro generator. Way Laai and Way Lami. So, we need to know what is turbines type to suit both of river Way Laai and Way Lami. We used the same method with other research that used TURBNPRO software for helping in the design of Turbines. The simulation result gives one alternative to the right turbine design for Way Laai is the orientation vertical of 6 jet Pelton with a peak efficiency of 89.9%. The right alternative turbine design for Way Lami is the vertical orientation Axial turbine/ propeller design with a peak efficiency of 93.3%.